Pengaruh BI Rate dan Jumlah Simpanan Masyarakat terhadap Penyaluran Kredit pada Bank Umum Pemerintah di Bali Periode 2013.I–2017.IV - Ni Luh Putu Basrita Sutasari; Gede Aryawan; A. A. Sri Purnami (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2018)
Credit is a financial facility that allows a person or business entity to borrow money to buy a product and repay it within a specified period of time. UU no. 10 of 1998 states that credit is the provision of money or equivalent claims, based on an agreement or agreement between banks and other parties that requires the borrower to repay the debt after a certain period of time with interest. This research discusses the influence both simultaneously and partially of the BI Rate and the amount of public deposits on lending to Government Commercial Banks in Bali. This test method used to test the hypothesis is multiple linear regression. The results of the analysis state that the BI Rate and Amount of Community Savings simultaneously have a significant effect on Lending to Government Commercial Banks in Bali. Partial BI Rate value does not have a significant effect (not significant) and the Public Savings Amount partially has a significant (significant) effect on Credit Distribution at Government Commercial Banks in Bali. The Value of Amount of Community Savings has a positive and significant influence on Credit Distribution at Commercial Banks in Bali Province.